2006
DOI: 10.1159/000089472
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Dysfunction and Pulmonary Hypertension in Sickle Cell Anemia: Is There a Role for <i>L</i>-Carnitine Treatment?

Abstract: Clinical manifestations of cardiovascular abnormalities in patients with sickle cell (SC) anemia are well documented. Many variables were assessed in our study before and after administration of L-carnitine to randomly selected 37 SC disease (SCD) children for a period of 6 months. Variables such as weight, height, serum ferritin levels, units of blood transfused and the number of veno-occlusive crises all showed significant improvement after the 6 months of therapy with L-carnitine. Our study also showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 66 publications
3
14
0
Order By: Relevance
“…In the present study, LVEDD decreased in group B. This is in agreement with the aforementioned study in patients with sickle cell anemia that found that cardiac diastolic function was improved after 6-month treatment with l-carnitine (28).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, LVEDD decreased in group B. This is in agreement with the aforementioned study in patients with sickle cell anemia that found that cardiac diastolic function was improved after 6-month treatment with l-carnitine (28).…”
Section: Discussionsupporting
confidence: 93%
“…l-Carnitine could therefore be effective in alleviating pulmonary hypertension in patients with thalassemia intermedia possibly through reduction in hemolysis and anemia. This is in agreement with the finding observed in the study in patients with sickle cell anemia that l-carnitine administration resulted in improvement of pulmonary artery pressure (28). We noted a significant increase in PAT in group-C patients, who were receiving magnesium chloride and hydroxyurea simultaneously.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…SCD is a hypercoagulable state. Studies show that SCD patients have elevated steady-state plasma levels of circulating tissue factor [529] and PAI-1, both of which further increase during sickle vaso-occlusive crises [530, 531]. Elevated PAI-1 has been implicated in primary PHT [509, 510].…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…In addition propionyl-L-carnitine increased eNOS protein expression in the same animal model (38). Lastly, two recent small studies on children with sickle cell disease and β-thalassemia associated PAH, suggested a benefit of L-carnitine therapy in decreasing pulmonary artery systolic pressure (39, 40). …”
Section: Discussionmentioning
confidence: 99%